New Characeae (Charophyceae, Charales) report in eastern Sicily (Italy) - Ilaria Pagana; Alessandra Virzì; Manuel Andrea Zafarana; Giuseppina Alongi (Italian Botanist)
Nowadays species belonging to the green algal family Characeae are highly endangered. For this reason, many of them are protected by European directives and included in Red Lists. In Italy, however, the Red List of Characeae does not exist and the distribution of these species is often unknown, especially in Sicily wetlands. In this study, we investigated the distribution and morphology of Characeae in fresh and brackish water wetlands, both natural and artificial, located in various areas of eastern Sicily (Italy). During the survey Chara globularis Thuiller, Chara vulgaris Linnaeus, Nitella capillaris (Krocker) J.Groves & Bullock-Webster, and Tolypella glomerata (Desvaux) Leonhardi were found. This is the first record of these species in the investigated sites. The results improved the knowledge of freshwater algal biodiversity in Sicily and, above all, allowed to fill distribution gaps of the Characeae species, to apply adequate protection measures and create national Red Lists of Characeae.